PELATIHAN PENGEMBANGAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA KURIKULUM MERDEKA DI KOTA PROBOLINGGO - Cahyanto, Bagus; Anies Fuady (LPPM STAI Muhammadiyah Probolinggo, 2025)
The curriculum plays a fundamental role in determining the direction and achievement of educational goals. The Merdeka Curriculum is designed to emphasize the formation of the Pancasila Student Profile, one of the implementations of which is carried out through the Pancasila Student Profile Strengthening Project (P5). In the implementation of the Pancasila Student Profile Strengthening Project (P5), teachers play a crucial role in ensuring its success in educational units. Therefore, this community service activity is held in the form of training to provide a deeper understanding of the development of the Pancasila Student Profile Strengthening Project (P5) in Probolinggo City as a preparatory step for educational units and teachers in implementing the Merdeka Curriculum. This training is designed in several stages including preparation, implementation, and evaluation to determine the success of the Pancasila Student Profile Strengthening Project (P5) development training program. This activity was attended by supervisors from the Probolinggo City Education and Culture Office, school principals, and teachers from various kindergarten institutions in the Mayangan District, Probolinggo City. The results of this activity show an increase in participants' understanding of the concept and implementation of the Pancasila Student Profile Strengthening Project (P5), and provide real benefits for participants in applying the Independent Curriculum in their educational units.